Ha Tinh province invests in climate-smart agriculture with potential to benefit over 200.000 farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The combined work under the CCAFS-funded climate-smart village project with agroclimate information services and climate-smart agriculture has been taken up in strategies, policies and projects in Ha Tinh province. The key changes are: improved seasonal forecasts are shared between departments and reach farmers. Commune governments co-invest through New Rural Development Program. Province Farmers' Union includes climate-smart agriculture in the five-year strategy 2018-2013, This means a potential to reach the province’ over 200,000 farmers.